Changes in species composition, phenology and distribution of wintering waders in the Azov-Black Sea region, Ukraine during the last 50 years - Diadicheva, E.A.; Zhmud, M.E. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2013)
The changes in species composition and phenology of wintering waders are analyzed in key areas of the Azov-Black Sea Region of Ukraine for the last 50 years, based on author's own data and published winter bird censuses. In recent decades, an increase in species diversity of waders that occur in winter on the Azov-Black Sea coast of Ukraine was observed (from 10 to 32 species for the past 50 years), as well as an increase in the length of their stay in the region, number of wintering areas and the expansion of their winter distribution. In this case, it is clearly seen a promoting of new wintering species in the Ukrainian sector of the Azov-Black Sea coast from the west to the east. There is a significant effect of weather and climate conditions in the December-January period on the species composition of wintering waders, wintering regularity, numbers and duration of stay in the region of some wintering species. The highest rates of species diversity and numbers of wintering waders were in years with positive monthly average temperatures at the same time in December and January. Considering the steady trend of gradually increasing the average temperature in December in the last decade, combined with the high average temperature in January in some years, the changes noted on the wintering grounds related to climate warming. Зміни видового складу і фенології зимуючих куликів протягом останніх 50 років проаналізовані на ключових територіях Азово-Чорноморського регіону України, виходячи з авторських даних і опублікованих матеріалів зимових обліків птахів. Відзначено збільшення видового різноманіття куликів, що зустрічаються в зимовий період на Азово-Чорноморському узбережжі України (з 10 до 32 видів), а також виявлено зростання тривалості перебування в регіоні ряду видів і розширення областей їх зимового розповсюдження. При цьому добре простежується просування нових зимуючих видів в український сектор Азово-Чорноморського узбережжя із заходу в східному напрямку. Виявлено суттєвий вплив погодно-кліматичних умов у груднево-січневий період на видовий склад зимуючих куликів, регулярність зимівель, чисельність і тривалість зимового перебування в регіоні окремих видів. Найбільші показники видового різноманіття та зимової чисельності куликів визначені в роки з позитивними середньомісячними температурами одночасно в грудні і січні. Враховуючи стійку тенденцію до поступового підвищення середньомісячної температури грудня в останні десятиліття, у поєднанні з високими середньомісячними температурами січня в окремі роки, відмічені зміни на зимівлях пов’язані з потеплінням клімату. Изменения видового состава и фенологии зимующих куликов в течение последних 50 лет проанализированы на ключевых территориях Азово-Черноморского региона Украины, исходя из авторских данных и опубликованных материалов зимних учетов птиц. Отмечено увеличение видового разнообразия куликов, встречающихся в зимний период на Азово-Черноморском побережье Украины (с 10 до 32 видов), а также отмечен рост продолжительности пребывания в регионе ряда видов и расширение областей их зимнего распространения. При этом хорошо прослеживается продвижение новых зимующих видов в украинский сектор Азово-Черноморского побережья с запада в восточном направлении. Выявлено существенное влияние погодно-климатических условий в декабрьско-январский период на видовой состав зимующих куликов, регулярность зимовок, численность и продолжительность зимнего пребывания в регионе отдельных видов. Наибольшие показатели видового разнообразия и зимней численности куликов отмечены в годы с положительными среднемесячными температурами одновременно в декабре и январе. Учитывая устойчивую тенденцию к постепенному повышению среднемесячной температуры декабря в последние десятилетия, в сочетании с высокими среднемесячными температурами января в отдельные годы, отмеченные изменения на зимовках связанные с потеплением климата.